Dual-purpose cowpea for West Africa - Tarawali, Shirley A.; Okike, Iheanacho; Kristjanson, Patricia M.; Singh, B.B. (2005)
Cowpea (Pzgna unguiculata) is grown as an intercrop with cereals in some 9 M ha of West Africa, mostly in the dry savanna. Though grain yields are low (circa 500 kg/ha), it is a nutritious food and dry season fodder. The haulms (leaves and stems) are cut and stored after grain harvest. Cowpea aids soil fertility by fixing soil N and returning N via manure from ruminants fed with haulms. Up to the early 1990s, research had focused on developing high grain yielding varieties. Recognition of farmers' appreciation of multiple uses, in particular the fodder value and the increasing importance of crop residues as feed resources in much of West Africa, where expansion of agricultural land and intensification mean reduced availability of land for planted forages, led to joint research by ILRI and IITA from 1994, which identified "dual purpose" varieties with the potential to provide both good grain yields and quality fodder under farmer conditions. Taking account of the heterogeneity in terms of market access and population density, two factors likely to influence adoption of dual purpose cowpea, this study estimated that, of the 9 M ha of cowpea, dual purpose varieties could be adopted on a consolidated area of 1.4 M ha of West Africa and potentially benefit 9.3 M people. Dual purpose cowpea varieties enable farmers with little land to obtain human food and livestock feed from the same area. Cowpea has also other economic, ecological and social benefits.